KEBIJAKAN PEMERINTAH INDONESIA DALAM MELINDUNGI PETANI LOKAL DARI ANCAMAN IMPOR KEDELAI AMERIKA SERIKAT TAHUN 2012-2016 - Susi Sinta Wulandari; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aims to explain the policy of Indonesian government in protected domestic farmer from the threat of soybean import by United State of America in 2012-2016. The aims of Indonesia government made a policy to protected domestic farming a result of dependence on imported soybean, the high of domestic soybean prices. And increase production of domestic soybean so consumption of domestic soybean can be fulfilled.The theory used in this research is Theory of import policy by Alexander Hamilton, concept national interest by Hans J. Morgenthau, and concept of food security. The author used Merchantilism approach from Friedrich List and nation-state level analyze. Data of this research was obtained from books, journals, articles, official documents and websites that support the hypothesis.The result of this research shows that there is an economic politic interest in the policy of Indonesian government for soybean import by United State of America. The made for give protection to domestic farmer from dependence on imported soybean, fluctuation of domestic soybean price have been increasingly and to increase the production of domestic. Because whit the presence of that policy, domestic farmer will pushed in increasing of domestic soybean production and soybean import no longer flooded the national market.Keywords: Policy, Import, National Interest, Dependence of Import